2018
DOI: 10.1007/s10096-017-3169-3
|View full text |Cite
|
Sign up to set email alerts
|

Oral teicoplanin versus oral vancomycin for the treatment of severe Clostridium difficile infection: a prospective observational study

Abstract: The aim of this study was to compare clinical cure rate, recurrence rate and time to resolution of diarrhea in patients with severe and severe-complicated Clostridium difficile infection (CDI) treated with teicoplanin or vancomycin. This two-year prospective observational study included patients with first episode or first recurrence of CDI who had severe or severe-complicated CDI and were treated with teicoplanin or vancomycin. Primary outcomes of interest were clinical cure rate at discharge and recurrence r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 36 publications
0
12
0
2
Order By: Relevance
“…Teicoplanin, though not approved for use in the US, is used as a treatment for CDI in Europe. A recent study found that teicoplanin may be the preferred choice for patients with severe CDI, because patients treated with teicoplanin had significantly lower recurrence rates than those treated with vancomycin (5, 50). As the use of teicoplanin as a treatment for CDI increases, care should be taken to consider the intrinsic sub-clinical teicoplanin resistance conferred by vanZ1 and the potential for selection of increased VanZ1 production as a mechanism of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Teicoplanin, though not approved for use in the US, is used as a treatment for CDI in Europe. A recent study found that teicoplanin may be the preferred choice for patients with severe CDI, because patients treated with teicoplanin had significantly lower recurrence rates than those treated with vancomycin (5, 50). As the use of teicoplanin as a treatment for CDI increases, care should be taken to consider the intrinsic sub-clinical teicoplanin resistance conferred by vanZ1 and the potential for selection of increased VanZ1 production as a mechanism of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Among 510 patients treated in this hospital from 2008-2013, the reported recurrence and case fatality rates were 8.4% and 6.3%, respectively (3). More severe forms of CDI and a notably higher recurrence rate were observed among patients treated in the same hospital from 2013-2015 (6). This suggested a potential outbreak of the ribotype 027 and emphasized the need for an analysis of the distribution of the C. difficile ribotypes among patients in Serbia.…”
Section: Introductionmentioning
confidence: 92%
“…The reports on C. difficile in Serbia are scarce (3)(4)(5)(6)(7)(8)(9)(10)(11). Since 2008, the University Hospital for Infectious and Tropical Diseases of the Clinical Center of Serbia in Belgrade has been the central Serbian institution for the treatment of patients with CDI (3).…”
Section: Introductionmentioning
confidence: 99%
“…The number of recurrences was, however, lower (7% v 16%) but the difference was not statistically significant; however, the study was not powered to answer this question. A prospective observational study compared vancomycin with teicoplanin in patients with severe infection 115. Treatment with teicoplanin resulted in higher clinical cure rate (90.7% versus 79.4%) and fewer recurrences (9.3% v 34.3%), both percentages reaching statistical significance.…”
Section: Treatmentmentioning
confidence: 99%